NON-CLASSICAL PROBLEM OF BEND OF AN ORTHOTROPIC ANNULAR PLATE OF VARIABLE THICKNESS WITH AN ELASTICALLY CLAMPED SUPPORT - Kirakosyan, R.M.; Stepanyan, S.P. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
A model of elastically clamped support for an inner edge of an axisymmetric annular round bending plate is proposed. Values of parameters of the support as well as relationship between them is determined. With the collocation method the problem of bending of a cylindrically orthotropic annual plate of a variable thickness under a uniformly distributed load is solved taking into account the transverse shear. It is assumed that the inner edge of the plate is elastically fastened and the outer one is hingedly supported. Based on the analysis of calculated values of immeasurable quantities qualitative conclusions are drawn.
Keywords: elastically clamped support, cylindrical orthotropy, variable thickness, transverse shear